2006
DOI: 10.1152/ajpheart.00240.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic nervous system contributes to the age-related impairment of flow-mediated dilation of the superficial femoral artery

Abstract: The physiological aging process is associated with endothelial dysfunction, as assessed by flow-mediated dilation (FMD). Aging is also characterized by increased sympathetic tone. Therefore, the aim of the present study is to assess whether acute changes in sympathetic activity alter FMD in the leg. For this purpose, the FMD of the superficial femoral artery was determined in 10 healthy young (22 +/- 1 yr) and 8 healthy older (69 +/- 1 yr) men in three different conditions: 1) at baseline, 2) during reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 41 publications
3
61
1
Order By: Relevance
“…[26][27][28] However, sympathetic nervous system activity is more effective in controlling resistance vessels than conduit arteries, where it has limited impact on baseline diameter. 29 In any case, impacts of changes in the sympathetic nervous system or circulating factors would arguably be similar between the limbs, and our experimental approach involving simultaneous bilateral measurements effectively eliminates such factors.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] However, sympathetic nervous system activity is more effective in controlling resistance vessels than conduit arteries, where it has limited impact on baseline diameter. 29 In any case, impacts of changes in the sympathetic nervous system or circulating factors would arguably be similar between the limbs, and our experimental approach involving simultaneous bilateral measurements effectively eliminates such factors.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups also suggested a relationship between vation induced by the cold pressor test, a potent nonbarorefl ex sympathoexcitatory stimulus, 35) whereas modifi cation did occur in older healthy subjects. 36) Conversely, it has been demonstrated that ANS denervation alters endothelial function in animal studies. 37) In humans, ANS modulation by alpha2-adrenoreceptor agonists has also been shown to improve endothelial dysfunction in patients with hypertension.…”
Section: Correlations Between Impairments In the Ans And Endothelial mentioning
confidence: 99%
“…However, to date, the only study using a detraining protocol to assess systemic adaptations involved spinal cord injury (SCI) patients. 13 Spinal cord injury patients experience progressive decreased vascularization after injury; the specific relative contribution of detraining or SCI to systemic vascular remodeling in this population remains unclear.…”
mentioning
confidence: 99%